DETERMINANTS OF MILLENNIAL INVESTMENT DECISION-MAKING IN THE SHARIA CAPITAL MARKET: A COMPREHENSIVE REVIEW - Aeni, Nurul Nur; Tubastuvi, Naelati; Purwidianti, Wida; Utami, Restu Frida (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: The study aims to examine the impact of financial literacy, overconfidence, regret aversion bias, herding, and risk tolerance on the investment decisions of the Indonesian millennial generation. Methods: The study used a quantitative approach with a sample of 120 respondents from the millennial generation who invested in the Islamic capital market. A statistical test was done using SPSS IBM 26. Results: Financial literacy and overconfidence significantly influenced investment decisions. On the other hand, regret aversion bias, herding, and risk tolerance had no significant impact on investment decisions. Conclusion and suggestion: The study concluded that financial literacy and overconfidence are the major factors that affect the investment decisions of the Indonesian millennial generation. The government (regulator) and related institutions should take a more proactive approach in providing outreach and education about the importance of financial literacy and overconfidence. The millennial generation is interested in investing in the Sharia capital market.